Contribution of Industrial Work Practice Performance and Creativeness to the Academic Skill and Its Effect to the Outcome of Skill Competency Test of Computer and Network Technology Skill Package in Vocational High School - Ayu Septiana Pratiwi; Dwi Agus Sudjimat; Hakkun Elmunsyah (Journal of Education and Vocational Research, 2017)
Abstract: Skill Competency Test (UKK-Uji Kompetensi Keahlian) is one educational programme in Vocational High School to assess student’s competency and skill as with the skill competency. Competency and skill students can be influenced by many factors. These can come from industrial work practice in DU/DI, a students creativity, and academic skill from learning activity in shcool. The study aims to reveral the contribution of several factor that affect to the outcome of skill competency in Vocational High School. Among factors that have been selected to be investigated is the industrial work practice in DU/DI, a students creativity, and cademic skill from learning activity in shcool. This study uses a quantitative approach. The research population was students at 12th Grade of Computer and Network Technology Skill Package in Vocational High School of Tulungagung Regency for 293 students, is Vocational High School 1 Boyolangu, Vocational High School 1 Rejotangan, Vocational High School Sore Tulungagung, Vocational High School Veteran Tulungagung. Sample taking technique in this research used proportional random sampling. The research sample was 169 students. Data collection of this study is using instrumen test for academic skill, questionnaire for creativity and documentation for industrial work practice performance and outcome of skill competency. Data analysis is using descriptive analysis and path analysis with SPSS for windows on significant 0, 05. The results of this study: (1) there is a significant contribution between industrial work practice to the academic skill was 0,09(9%); (2) there is a significant contribution between creativity to the academic skill was 0,003(3%); (3) there is a significant contribution between industrial work practice to the outcome of skill competency was 0,025(2,5%); (4) there is a significant contribution between creativity to the outcome of skill competency was 0,002(2%); and (5) there is a significant contribution between academic skill to the outcome of skill competency was 0,003(3%). The conclution of this research is outcome of skill competency can be affected from industrial work practice, creativity and academis skill.Keyword: Industrial work practice, creativeness, academic skill, outcome of skill competency test of computer